Design of Smart Solar Panel System as a Source of Electrical Energy - Syafitri, Ayu; Pramudia, Bagas; Eriansyah, Fadillah; Tiara; Sinek Mehuli Br PA; Meiliyani Br Ginting (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
Designing a smart solar panel system as a source of electrical energy is an important step in facing increasing global energy challenges and climate change. The system combines sustainable solar panel technology with smart elements that enable more efficient energy use and management. The advantages of smart solar panel systems include the ability to produce clean electrical energy and reduce long-term operational costs. By utilizing smart technology, users can monitor and optimize their energy use in real time, reduce waste, and minimize environmental impact. However, there are also several challenges that need to be overcome, including high initial costs, dependence on weather conditions and sunlight intensity, and limitations in energy storage. REFERENCES Anantama, A., Apriyantina, A., Samsugi, S., & Rossi, F. (2020). Alat Pantau Jumlah Pemakaian Daya Listrik Pada Alat Elektronik Berbasis Arduino Uno. Jurnal Teknologi Dan Sistem Tertanam, 1(1), 29. https://doi.org/10.33365/jtst.v1i1.712 Darmayanti, I., Ikhsan, A. N., Utami, D. A. B., & Subarkah, P. (2022). Implementasi Memory Game di MIT App Inventor. Jurnal Ilmiah Diseminasi Teknologi Informasi, 8(2). Eka Saputra, Y. M. D., Ramadhan, M. T. N., Maulida, A., Santoso, B., & Basri, I. (2024). Design a Smart Solar Tracker to Increase Energy Output Power Generated in Solar Home System. MOTIVATION : Journal of Mechanical, Electrical and Industrial Engineering, 6(1), 53–62. https://doi.org/10.46574/motivection.v6i1.286 Erianto, B., & Haryudo, S. I. (2023). Perancangan Panel Surya untuk Kebutuhan Darurat Rumah Tinggal dengan Sistem Switch. Jurnal Teknik Elektro, 12. Gunawan, I., Akbar, T., & Anwar, K. (2019). Prototipe Sistem Monitoring Tegangan Panel Surya (Solar Cell) Pada Lampu Penerang JalanBerbasis Web Aplikasi. Infotek : Jurnal Informatika Dan Teknologi, 2(2). Haryanto, D., William, G., Purusotama, I. K. G., Dwiki, D., & Sumarta, R. P. (2024). Sustainable Energy for Sorong’s Fishermen: Solar Panel Technology Implementation. Proceeding of International Conference on Artificial Intelligence, Navigation, Engineering, and Aviation Technology (ICANEAT), 1(1), 147–149. https://doi.org/10.61306/icaneat.v1i1.223 Mujiraharjo, F. N., & Basuki, M. (2019). ANALISIS INDEKS KEPUASAAN MASYARAKAT TERHADAP PELAYANAN PUBLIK BIDANG KESEHATAN (Studi Kasus: Faskes Tingkat I Mojokerto). Jurnal Desiminasi Teknologi, 7(2). Mungkin, M., Satria, H., Yanti, J., Turnip, G. B. A., & Suwarno, S. (2020). Perancangan Sistem Pemantauan Panel Surya Pollycristalline Menggunakan Teknologi Web Firebase Berbasis IoT. INTECOMS: Journal of Information Technology and Computer Science, 3(2), 319–327. https://doi.org/10.31539/intecoms.v3i2.1861 Pratidhina, E., Kuswanto, H., & Rosana, D. (2021). Penggunaan Arduino Uno dan Common-Coding pada Percobaan Fisika Materi Kelistrikan. Cipta Media Nusantara (CMN). Purwoto, B. H., Jatmiko, J., Fadilah, M. A., & Huda, I. F. (2018). Efisiensi Penggunaan Panel Surya sebagai Sumber Energi Alternatif. Emitor: Jurnal Teknik Elektro, 18(1), 10–14. https://doi.org/10.23917/emitor.v18i01.6251 Rudiyanto, B., Rachmanita, R. E., & Budiprasojo, A. (2023). DASAR DASAR PEMASANGAN PANEL SURYA. Unima Press. Safitri, N., Rihayat, T., & Riskina, S. (2019). Teknologi Photovoltaic. Yayasan Puga Aceh Riset. Samania, N., Nirsal, & Fa’rifah, R. Y. (2020). RANCANG BANGUN APLIKASI E-VOTING PEMILIHAN KETUA UMUM HIMPUNAN MAHASISWA INFORMATIKA (HMTI) UNIVERSITAS COKROAMINOTO PALOPO BERBASIS WEBSITE. D’computare: Jurnal Ilmiah Teknologi Informasi Dan Ilmu Komputer, 10(1). https://doi.org/10.30605/dcomputare.v10i1.27 Samsurizal, Mauriraya, K. T., Fikri, M., Pasra, N., & Christiono. (2021). PEMBANGKITLISTRIK TENAGASURYA (PLTS) (R. Hidayawanti, Ed.). Institut Teknologi PLN. Sari, I. P., Tria Siska, S., & Budiman, A. (2021). Perancangan Aplikasi Pelayanan Gangguan Tv Kabel Berbasis Web Dan Sms Gateway. Jurnal Pusat Akses Kajian Teknologi Artifical Intelligence, 1(1), 20–28. Satria, A., Mukram, M. H., Pratama, C., & Sutabri, T. (2024). Dampak dan Tantangan Implementasi Smart Sistem. IJM: Indonesian Journal of Multidisciplinary, 2(1). Sinurat, E. C., & Bella, C. (2022). RANCANG BANGUN ROTASI MATAHARI PADA PANEL SURYA DENGAN MENGGUNAKAN ARDUINO UNO (STUDI KASUS ROTASI PANEL SURYA). 2. Suhendra. (2022). DASAR – DASAR PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA. Media Edukasi Indonesia.